Bio-inspired hybrid scaffold of zinc oxide-functionalized multi-wall carbon nanotubes reinforced polyurethane nanofibers for bone tissue engineering. (5th November 2017) - Shrestha, Bishnu Kumar; Shrestha, Sita; Tiwari, Arjun Prasad; Kim, Jeong-In; Ko, Sung Won; Kim, Han-Joo; Park, Chan Hee; Kim, Cheol Sang
Abstract: In this study, we prepared nanotopographical polyurethane (PU)-based bioactive scaffolds that incorporated uniformly dispersed functionalized multi-wall carbon nanotubes ( f MWCNTs) and zinc oxide (ZnO) nanoparticles (NPs) using an electrospinning technique. We found that well dispersed f MWCNTs along with ZnO NPs reinforced PU fibers demonstrated significant improvement in mechanical strength, hydrophilicity, thermal stability, electrical conductivity, degradability, biomineralization, and biocompatibility. Inspired by the exciting nature of biopolymeric composite (PU/ZnO- f MWCNTs) membranes, these hybrid scaffolds offer extensive interest to tissue engineering as a potential biomedical application. The specific bioactive properties and cell-biomaterial interaction of electrospun scaffold containing 0.2 wt% ZnO with 0.4 wt% f MWCNTs were found to demonstrate anti-bacterial activity and cytocompatibility. Furthermore, the highly charged density, large surface-to-volume ratio, and more functional groups in f MWCNTs integrated on the scaffolds promote osteogenic differentiation of pre-osteoblast (MC3T3-E1) cells. Therefore, the novel as-prepared multifunctional electrospun fibrous scaffold could suggest new avenues for exploration as promising osteoproductive and osteoinductive biomaterials that offer great benefit to bone tissue engineering. Graphical abstract: Highlights: Functionalized multi-wall carbon nanotubes ( f MWCNTs) within nanofiber enhance the electrical conductivity of scaffolds. The f MWCNTs (0.4 wt%) in scaffolds show good antibacterial activity. Interaction of zinc oxide and f MWCNTs with simulated body fluid resulting nucleation of calcium phosphate. The bioscaffolds exhibit excellent platform for osteogenic differentiation of pre-osteoblastic cells.